Response of steroid‐refractory chronic graft‐versus‐host disease to extracorporeal photopheresis correlates with the dose of CD3+ lymphocytes harvested during early treatment cycles. Issue 2 (10th October 2015) - Bertani, Giambattista; Santoleri, Luca; Ferri, Ursula; Marenco, Paola; Grillo, Giovanni; Zucchetti, Elisa; Forno, Barbara; Lando, Giuliana; Scarpati, Barbara; Cairoli, Roberto; Rossini, Silvano; Cesana, Clara
Abstract : BACKGROUND: Extracorporeal photopheresis (ECP) is a recognized second‐line treatment for steroid‐refractory chronic graft‐versus‐host disease (cGVHD). Treatment course is usually long, expensive, and demanding for patients, so predictors for response are needed. We carried out a retrospective study on cGVHD patients treated at our institution with the aim to identify a possible correlation between apheretic yields composition and probability of response. STUDY DESIGN: Patients treated for at least 6 months were eligible for the study. Flow cytometry data, including absolute counts of lymphocytes and their subpopulations in ECP products from cGVHD patients, were collected. For each cell population 1) the median dose per procedure harvested during the first 3 months of treatment and 2) the cumulative dose collected in the same period were compared with clinical response. RESULTS: A total of 726 ECP procedures were performed in 15 patients. Overall response, defined as either a complete response (CR) or a partial response according to National Institutes of Health criteria, was obtained in 10 of 15 patients (66.7%), and CR, in eight of 15 (53.3%). According to Cox regression analysis, the probability of achieving an overall response is significantly correlated with the median number of CD3+, CD3+CD4+, and CD3+CD8+ lymphocytes collected during the early treatment phase (first 3 months). CONCLUSION: Our data suggest that CD3+ cell evaluation in ECP during the early phase of treatment course could predict response and help identify patients who deserve further treatment.